2019
DOI: 10.19175/recom.v9i0.3011
|View full text |Cite
|
Sign up to set email alerts
|

Compreensão da relação interpessoal enfermeiro-paciente em uma unidade de atenção primária fundamentada em Imogene King

Abstract: Objetivo: compreender a relação interpessoal entre o enfermeiro e o paciente, sob a ótica do sistema interpessoal de Imogene King. Método: estudo qualitativo com dois grupos focais realizados em uma Unidade de Atenção Primária à Saúde. Os dados foram analisados por categorização temática tendo como arcabouço teórico analítico o Sistema Interpessoal do Modelo Conceitual de Sistemas Abertos. Resultados: As análises permitiram a formulação de três categorias: 1) ações da interação e comunicação impulsionadoras da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
3
0
4
Order By: Relevance
“…11 The interest of nursing professionals, on the other hand, may come from the close relationship established with the patient, since the construction of bonds is favored by the effectiveness of care. 12 In analyzing the categories constructed from the attributes, it is observed that they involve two distinct, but complementary, approaches. The first refers to the system model used, which includes the organizational structure, and the second refers to the work process, which covers the practical domain, involving the performance of the actors in the care process -health professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 The interest of nursing professionals, on the other hand, may come from the close relationship established with the patient, since the construction of bonds is favored by the effectiveness of care. 12 In analyzing the categories constructed from the attributes, it is observed that they involve two distinct, but complementary, approaches. The first refers to the system model used, which includes the organizational structure, and the second refers to the work process, which covers the practical domain, involving the performance of the actors in the care process -health professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the therapeutic bond between nurse and care receivers, established through communication, is emphasized as a potentiality to strengthen information sharing and confidence on care planning. The interpersonal relations of subjects cross-section in moments of imbalance and stress, thus directing quality care actions whose goals will have a higher chance of being fulfilled (28) . Thus, when PLHIV are observed within PHC, the interpersonal system of the Theory of Goal Attainment reinforces a holist outlook towards the patient, beyond the disease context.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the face of a proposed treatment, the nurse can act with the patient, guiding them about the disease and its complications in the short-, medium-and long-term, as well as the benefits arising from the achievement of health goals 13 . The individual's involvement and participatory behavior in the face of the established therapeutic plan, collaboratively with the nurse, contribute to decision-making about one's own health and the achievement of goals 14 . In this context, the professional must negotiate priorities, monitor adherence, motivate participation, and stimulate the patient's effort in managing their treatment 1 .…”
Section: Discussionmentioning
confidence: 99%